Risk factors associated to multi drug resistant tuberculosis in Marginal Urban Public Health Centers 2006-2008 - Crispín, Víctor (2012)
Tuberculosis (TB) is a public health problem, worsed by multidrugs resistant forms (MDR-TB). The control of MDR-TB require a well definition of patient epidemiological situation before start treatment and clarify the rol of different risk factors associated to MDR-TB . The objectives were to determine the associated factors to MDR-TB in urban marginal health public centers from East Lima. This is an observational and analytical case-control study, age and gener matched, undertaken since 2006 to 2008. We defined as case all patients who were diagnosticated and treated to MDR-TB and as control all patients who were recuperated from tuberculosis with primary scheme. The data was acquired from the routine reports of the National Control Program. 252 patients were incorporated, 126 cases and 126 controls. 108 (85,7%) controls and 19 (15%) cases were new. 45 (36%) cases were failures to previous treatment with primary scheme and 28 (22%) had history of contacts with MDR-TB patients. The personal TB antecedent (OR = 28; CI 95%: 21,1 – 34,9, p < 0,005), family TB-antecedent (OR = 1,68; CI 95%: 1,65 – 2,09, p < 0,05), have a deceased family member by tuberculosis (OR = 4,03; CI 95%: 3,04 – 5,02, p < 0,005), failure to previous treatment with scheme one or two (p < 0,01), the infraweith (OR = 4,95; CI 95%: 3,73 - 6,17, p < 0,005), and the condition of be new case, were factors associated to MDR-TB.